About levitation of superconducting rings for magnetic system of multipole plasma trap - Bishaev, A.M.; Bush, A.A.; Behtin, M.A.; Gavrikov, M.B.; Gordeev, I.S.; Bugrova, A.I.; Kamentsev, K.Ye.; Kozintseva, M.V.; Savel’ev, V.V.; Safronov, A.A.; Shaposhnikov, M.I.; Smirnov, P.G. (Вопросы атомной науки и техники, 2013)
In order to continue works on creation of the plasma trap with levitating magnetic coils the analytical function of the potential energy U(x,θ) of the system of two coaxial superconducting rings (and the upper ring is fixed at that), which trapped given fluxes of the same sign, in the homogeneous gravity field versus the coordinate x of the free ring and the deflection angle θ of its axis from the vertical has been obtained under approximation of thin rings. For manufactured HTSC rings, which trapped fluxes of the same sign, with the help of calculations of the dependence U(x,θ) in Mathcad system, such values of magnetic fluxes trapped by rings have been obtained under which equilibrium states of the free ring in the field of the fixed ring, stable to the shift of the levitating ring plane along the common axis and to the deflection of its axis from the vertical, exist. The existence of the determined by calculations equilibrium state for HTSC rings under trapped fluxes of the same sign, stable to the vertical shifts of the levitating ring and to the deflection of its axis from the vertical, has been proved experimentally. В продолжение работ по созданию плазменной ловушки с левитирующими магнитными катушками в приближении тонких колец получено аналитическое выражение для потенциальной энергии U (x,θ) системы из двух коаксиальных сверхпроводящих колец (причем, верхнее из них закреплено), захвативших заданные потоки одного знака, в однородном поле силы тяжести как функции координаты x свободного кольца и угла отклонения θ его оси от вертикали. Для изготовленных ВТСП-колец, захвативших потоки одного знака, с помощью расчетов в системе Mathcad зависимости U (x,θ) были найдены такие значения захваченных кольцами магнитных потоков, при которых существуют равновесные состояния свободного кольца в поле закрепленного кольца, устойчивые по отношению к смещению плоскости левитирующего кольца вдоль общей оси и к отклонению его оси от вертикали. Существование найденного из расчетов равновесного состояния для ВТСП- колец при захваченных потоках одного знака, устойчивого по отношению к вертикальным смещениям левитирующего кольца и к отклонению его оси от вертикали, было подтверждено экспериментально. У продовження робіт зі створення плазмової пастки з левітуючими магнітними котушками в наближенні тонких кілець отримано аналітичний вираз для потенційної енергії U (x, θ) системи з двох коаксіальних надпровідних кілець (причому, верхнє з них закріплено), що захопили задані потоки одного знаку, в однорідному полі сили тяжіння як функції координати x вільного кільця і кута відхилення θ його осі від вертикалі. Для виготовлених ВТНП-кілець, які захопили потоки одного знаку, за допомогою розрахунків в системі Mathcad залежності U (x, θ), були знайдені такі значення захоплених кільцями магнітних потоків, при яких існують рівноважні стани вільного кільця в полі закріпленого кільця, стійкі по відношенню до зміщення площини левітуючого кільця уздовж загальної осі та до відхилення його осі від вертикалі. Існування знайденого з розрахунків рівноважного стану для ВТНП-кілець при захоплених потоках одного знаку, стійкого по відношенню до вертикальних зсувів левітуючого кільця та до відхилення його осі від вертикалі, було підтверджено експериментально.